Sofokleous, Konstantina - (:unkn) unknown (My University, 2026)
Konstantina Sofokleous holds a Postgraduate Title in Animation with Distinction from the University of Westminster (UK, 2006), a Certificate in Internet Technologies with Excellence from the New York University NYU (USA, 2001), and a BA Degree in Graphic Design from the Technological Educational Institute of Athens (Greece, 1996). Furthermore, she has received training in 3D Games & Virtual Cinematography from CIANT/FAMU of Prague (Czech Republic, 2006), and has attended courses and workshops in Fine Arts at the Central Saint Martins, University of the Arts London (UK, 2010/11/13/15/20). During her studies she was granted scholarships by the Fulbright Commission and the National Scholarship Foundation of Greece (IKY), and grants by the European programmes Comett II and MEDIA. Her Artwork has been exhibited, screened, and awarded at International Biennales, Contemporary Art Exhibitions, Video Art, Animation, Film, and New Media Art Festivals and Conferences around the world. In 2005, during her postgraduate studies, she represented Cyprus at the 51st Venice Biennale International Art Exhibition with the works 'Alice's Adventures in Wonderland' and 'Popular Children's Poem'. Her work has been featured in the International Press (Le Monde, Dall’ Oblio Polumnia, Lookout Magazine, Kunstbeeld Art Magazine, Plumart Magazine etc.), included in the Public Primary Education Art Curriculum and the Contemporary Art Collection of the Cyprus Ministry of Education and Culture, and analyzed in PhD and MPhil Research Papers of Universities abroad. Her research interests focus on Children’s Literature, Retelling of a Story and the Interpretation of the Written Word within the Visual Language, on Visual Music, Rhythm, and on Tradition.
Keywords: arts